Implementation of a Spine-Centered Care Pathway at a Regional Academic Spine Center. Issue 1 (January 2020) - Ghobrial, George M.; Wilson, Jefferson; Franco, Daniel; Vogl, Kristen; Vaccaro, Alexander R.; Harrop, James S.
Study Design: Retrospective case series. Objective: To describe the early implementation of an inpatient spinal surgery unit and measure the impact on cost and length of stay (LOS). Methods: A retrospective case review was performed for frequent spine-related diagnosis-related groups (DRGs) cared for by a dedicated multidisciplinary team: combined anterior/posterior (AP) spinal fusion with major complicating or comorbid condition (MCC), combined (AP) spinal fusion with CC, combined (AP) spinal fusion without complicating or comorbid (CC)/MCC, cervical spinal fusion with MCC, cervical spinal fusion with CC, and cervical spinal fusion without CC/MCC. Four time periods were compared: historical control, initial pathway implementation, full pathway implementation, and spine unit opening. Mean hospital LOS, mean and median total costs (USD), and ratio of costs-to-charges were analyzed. Results: The number of spine cases per interim ranged from 219 to 258. The mean overall hospital LOS and mean cost varied from 3.8 to 4.3 days for all DRGs across the time periods and was not significant. Cost also did not vary significantly throughout. Median variable cost per anterior/posterior spinal fusion procedure with a CC or MCC declined by 16 311, first with the institution of a spine pathway protocol by USD8738 and then USD7423 with the establishment of a spine care unit but did not reach significance. Conclusions: The use of a standardized, inpatient spine care pathway implemented by a multidisciplinary team may reduce the hospital length of stay and decrease overall costs.